2013
DOI: 10.1093/mp/sss126
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Analysis of Arabidopsis thaliana Histidine Kinase AHK5 Bound to Its Cognate Phosphotransfer Protein AHP1

Abstract: The multi-step phosphorelay (MSP) system defines a key signal transduction pathway in plants and many eukaryotes. In this system, external stimuli first lead to the activation of a histidine kinase, followed by transfer of a phosphoryl group from the receiver domain of the kinase (HK(RD)) to downstream, cytosolic phosphotransfer proteins (HPs). In order to establish the determinants of specificity for this signaling relay system, we have solved the first crystal structure of a plant HK(RD), AHK5(RD), in comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 53 publications
1
65
0
1
Order By: Relevance
“…This alignment allowed us to pinpoint few amino acid candidates according to their presence in the strong-interacting HPt group and absence in the non- or weak-interacting HPt group. Moreover, we used the solved structure of the Arabidopsis AHK5 RD /AHP1 complex [34] to focus our choice on the HPt helices known to interface with the RD (Figure S2). In this close relative complex, helices α2, α3 and α4 of AHP1 formed a groove where helix α1 from AHK5 RD can insert.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This alignment allowed us to pinpoint few amino acid candidates according to their presence in the strong-interacting HPt group and absence in the non- or weak-interacting HPt group. Moreover, we used the solved structure of the Arabidopsis AHK5 RD /AHP1 complex [34] to focus our choice on the HPt helices known to interface with the RD (Figure S2). In this close relative complex, helices α2, α3 and α4 of AHP1 formed a groove where helix α1 from AHK5 RD can insert.…”
Section: Resultsmentioning
confidence: 99%
“…So far, only two examples of solved structures of HK/HPt complexes in eukaryotes are present in the literature: the complex of yeast Sln1p RD with Ypd1p [45] and the Arabidopsis complex of AHK5 RD /AHP1 [34]. Unlike the classical idea proposing that HPt proteins can act as functionally redundant signaling hubs, we were convinced that HPt proteins could really play a role leading to response specificity in the MSP system.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Transport by protein-to-protein relay is frequently employed in nature to transfer reactive species or signaling molecules in both prokaryote and eukaryote cells. Examples include copper transport (60), electron transport (61), and relay of phosphoryl groups in signal transduction in plants (62), animals (63), and bacteria (64). In these examples, precise positioning of the donor and acceptor proteins is critical to cargo transfer, and both donor and acceptor proteins have co-evolved to perform efficient ligand transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the other AHKs, the signal detection by an input domain is less established but their involvement is proposed in mega-gametogenesis (Pischke et al, 2002), stomatal signaling (Desikan et al, 2008), salt regulation, resistance to bacterial and fungal infections (Pham et al, 2012) or drought stress (Urao et al, 1999;Tran et al, 2007). Given their role of shuttle proteins, the abilities of the five canonical AHPs (AHP1 to AHP5) to interact with upstream and downstream proteins of MSP were tested with in vivo and in vitro studies, what revealed that most AHK (Dortay et al, 2006;Pek arov a et al, 2011;Mira-Rodado et al, 2012;Bauer et al, 2013) and ARR (Imamura et al, 1999;Lohrmann et al, 2001;Dortay et al, 2006Dortay et al, , 2008Hor ak et al, 2008;Veerabagu et al, 2012) family members are partners of the majority of AHPs. However, it appears that AHK1 is, with a limited interacting ability, a singular receptor among them all.…”
Section: Introductionmentioning
confidence: 99%